Translating medical texts into a foreign language: some methodological considerations - Plested A., Maria Cecilia; Quiroz. H., Gabriel Angel; Muñoz, Carlos Arturo; Giraldo, John Jairo (HERMES - Journal of Language and Communication in Business, 2000)
Many authors, scholars, and theorists have theoretically denied the possibility of translating into a foreign language (Newmark, 1998, 1995; Van Deth, 1989; Vásquez-Ayora, 1977 among others), because of the interference caused by the translator’s mother tongue as well as the lack of competence, especially in writing, and level of intuition when going into the foreign language. Authors confront and argue the different points of view. Arguments in favor of translating into a foreign language should also be considered (Wilss, 1982; Wotjak, 1981; Harris, 1990; Nord, 1992; Cao, 1996; Beeby, 1996; Quiroz and Muñoz, 1996; Zapata et al. 1998). Likewise, it is shown that methods, methodologies, and techniques may be used both ways. It is concluded that the correct establishment of text analysis features as well as linguistic characteristics in both languages make it possible to translate medical texts into English as a for-eign language.